Why a “whack-a-mole” approach to widening participation won’t work - and what to do about it: a policy brief - Elisabeth Moores; Julian Crockford; Lizzy Woodfield; Liz Austen (Frontiers in Education, 2024)
Despite increasing access to higher education (HE) over the past two decades, students from disadvantaged backgrounds remain less likely to enter the most selective institutions, and less likely to achieve good outcomes. In England, providers that charge more than £6,000 a year tuition fees must have an Access and Participation Plan (APP) approved by the Office for Students (OfS). Plans aim to improve equality in student access, success, and progression. APPs typically focus on snapshots of equality gaps, inputs over outcomes, and individual institutions over collaborative efforts. These limitations encourage a “whack-a-mole” approach, reducing effectiveness of interventions. A more nuanced approach to evaluation is needed, together with increased and organized sector-wide collaboration, and acknowledgment of the dynamic operating context.